2006
DOI: 10.1089/lap.2006.16.418
|View full text |Cite
|
Sign up to set email alerts
|

Two Cases of Thoracoscopic Resection of Esophageal Duplication in Children

Abstract: We report two cases of thoracoscopic resection of esophageal duplication cysts. Both patients underwent successful thoracoscopic excision. They were discharged on postoperative day 2 and 4, respectively. They made uneventful recoveries and were completely asymptomatic at 1-month followup. One child was lost to long-term follow-up. In the other child, barium swallow study 10 months after surgery demonstrated a pseudodiverticulum at the site of cyst excision. Thoracoscopic resection of esophageal duplications is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…With regard to thoracoscopic resection, previous studies suggested enucleation of the cyst by electrocauterization or harmonic scalpel [1,8,9]. In our case, cystectomy was performed using endo-staplers.…”
Section: Discussionmentioning
confidence: 82%
“…With regard to thoracoscopic resection, previous studies suggested enucleation of the cyst by electrocauterization or harmonic scalpel [1,8,9]. In our case, cystectomy was performed using endo-staplers.…”
Section: Discussionmentioning
confidence: 82%
“…10 Presenting symptoms may include those of either respiratory or intestinal origin, including compression of the esophagus or trachea due to mass effect, pain, infection, bleeding, or perforation. 2,11 Most studies report the finding of a duplication cyst to be an unexpected finding in patients presenting with symptoms suggestive of acute appendicitis, intussusception, intestinal obstruction, or gastrointestinal hemorrhage. In many series, however, enteric cysts are asymptomatic and discovered incidentally on imaging or at the time of surgery for other indications.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 Complete excision is the treatment of choice for both symptomatic and asymptomatic, incidentally discovered esophageal duplication cysts. 2,6,12,13 Observation of these lesions should be discouraged given the potential for increasing size and compression of adjacent organs, bleeding, perforation, and malignant transformation. 2,6,12,14 Incomplete excision, needle aspiration, and marsupialization may all be complicated by unacceptably high rates of recurrence.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations